Stressful Newborn Memories: Pre-Conceptual, In Utero, and Postnatal Events - Papadopoulou, Zoe; Vlaikou, Angeliki-Maria; Theodoridou, Daniela; Markopoulos, Georgios S.; Tsoni, Konstantina; Agakidou, Eleni; Drosou-Agakidou, Vasiliki; Turck, Christoph W.; Filiou, Michaela D.; Syrrou, Maria (Frontiers in Psychiatry, 2019)
Early life stressful experiences are critical for plasticity and development, shaping adult neuroendocrine response and future health. Stress response is mediated by the autonomous nervous system and the hypothalamus-pituitary-adrenal (HPA) axis while various environmental stimuli are encoded via epigenetic marks. The stress response system maintains homeostasis by regulating adaptation to the environmental changes. Pre-conceptual and in utero stressors form the fetal epigenetic profile together with the individual genetic profile, providing the background for individual stress response, vulnerability or resilience. Postnatal and adult stressful experiences may act as the definitive switch. This review addresses the issue of how pre-conceptual in utero and post-natal events, together with individual differences, shape future stress response. Putative markers of early life adverse effects such as prematurity and low birth weight are emphasized and the epigenetic, mitochondrial and genomic architecture regulation of such events are discussed.